THE APPLICATION OF ENDOSCOPE AND IMAGE PROCESSING FOR DETERMINING REMAZOL RED DYE CONCENTRATION IN WATER SAMPLES (Jurnal Teknologi (Sciences & Engineering), 2022)
Remazol dyes are widely used in textile industry, which are then discharged to the environment as waste products. Studies on bioremediation and decolorization of dye waste normally employ expensive spectrometers or colorimeters. This study proposes a low-cost procedure to determine the concentration of Remazol red dye with the use of a digital endoscope and image processing technique. The concentration of Remazol red dye considered in this study ranges from 0.001 to 0.700 g/L. An endoscope is used to capture digital images of dye samples. Reg-green-blue (RGB) images of the samples are converted to grayscale images, which are then converted to a mean grayscale index (MGI). The MGI is then calibrated with real concentration of dye samples. Three calibration curves were developed for three different ranges of dye concentration of 0.001- 0.010 g/L, 0.020 – 0.100 g/L, and 0.100 – 0.700 g/L, with a coefficient of determination (R2) of 0.961, 0.9793, and 0.9903, respectively.